INFLUENCE OF LOCAL CULTURE ON QUALITY EMPLOYEE WORK AT PT. HADJI KALLA TOYOTA CITY PAREPARE - Rusmin Nuryadin; Yadi Arodhiskara; Sisni Miayu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2023)
This study aims: Hadji Kalla Toyota Parepare Branch (2) To find out the effect the meaning of the local cultural value